1999
DOI: 10.1046/j.1365-2044.1999.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Target‐controlled propofol vs. sevoflurane: a double‐blind, randomised comparison in day‐case anaesthesia

Abstract: SummaryWe compared target-controlled propofol with sevoflurane in a randomised, double-blind study in 61 day-case patients. Anaesthesia was induced with a propofol target of 8 mg.ml ¹1 or 8% sevoflurane, reduced to 4 mg.ml ¹1 and 3%, respectively, after laryngeal mask insertion and subsequently titrated to clinical signs. Mean (SD) times to unconsciousness and laryngeal mask insertion were significantly shorter with propofol [50 (9) s and 116 (33) s, respectively] than with sevoflurane [73 (14) s and 146 (29) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
3
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 28 publications
8
38
3
1
Order By: Relevance
“…Compared with intravenous anesthetics, volatile anesthetics are known to affect, besides GABA A receptors, a multitude of molecular targets in the spinal cord (Cheng and Kendig, 2000Wong et al, 2001;Campagna et al, 2003). Although the experimental conditions in vitro are different from the in vivo measurement of immobility, our results reflect closely those obtained from studies in humans in whom intravenous GABAergic anesthetics were far less effective in depressing involuntary movements compared with volatile anesthetics (Ashworth and Smith, 1998;Smith and Thwaites, 1999;Watson and Shah, 2000). However, in clinical study settings, immobility can also be achieved with intravenous anesthetics at concentrations approximately 5-fold higher than those required for hypnosis (Smith et al, 1994).…”
Section: Gabaergic Drugs Display a Limited Efficacy In Depressing Vensupporting
confidence: 72%
See 1 more Smart Citation
“…Compared with intravenous anesthetics, volatile anesthetics are known to affect, besides GABA A receptors, a multitude of molecular targets in the spinal cord (Cheng and Kendig, 2000Wong et al, 2001;Campagna et al, 2003). Although the experimental conditions in vitro are different from the in vivo measurement of immobility, our results reflect closely those obtained from studies in humans in whom intravenous GABAergic anesthetics were far less effective in depressing involuntary movements compared with volatile anesthetics (Ashworth and Smith, 1998;Smith and Thwaites, 1999;Watson and Shah, 2000). However, in clinical study settings, immobility can also be achieved with intravenous anesthetics at concentrations approximately 5-fold higher than those required for hypnosis (Smith et al, 1994).…”
Section: Gabaergic Drugs Display a Limited Efficacy In Depressing Vensupporting
confidence: 72%
“…General anesthetics like etomidate and propofol, which act almost exclusively via GABA A receptors, are potent hypnotics, but their efficacy in depressing spontaneous and evoked movements is clearly limited (Ashworth and Smith, 1998;Smith and Thwaites, 1999;Watson and Shah, 2000;Rudolph and Antkowiak, 2004;Grasshoff et al, 2006a). In clinical practice, these agents are routinely used for providing hypnosis and amnesia but rarely are administered to achieve immobility.…”
mentioning
confidence: 99%
“…The use of Nitrous oxide (N 2 O) may have produced some of these minor differences in the timing and duration of hypotension, as compared to our study where N 2 O was not used. Smith and Thwaites 14 in another study in 1999, using methods similar to ours, observed a significant difference in MAP, 1 minute after induction but not at other times, closely resembling our findings. Comparable results to ours were also obtained by Priya V et al 7 but the MAP difference was significant at 3 minutes after induction, possibly due to the administration of Fentanyl 2 µg/kg IV, immediately after the induction end point.…”
Section: Journal Of Society Of Anesthesiologists Of Nepalsupporting
confidence: 91%
“…Contrary to our study, HR was observed to increase slightly after induction possibly because analgesics were not administered prior to induction and airway was managed by holding a face mask after induction without muscle relaxation. However, Smith and Thwaites 14 in another study in 1999, demonstrated similar results to ours with a significant decrease in HR with sevoflurane at 3 and 5 minutes after induction. Priya V et al 7 and Jellish WS et al 8 et al observed a decrease in HR for both anesthetics up to several minutes after induction, but, in contrast to our study, the difference in HR between the two anesthetics was not statistically significant.…”
Section: Journal Of Society Of Anesthesiologists Of Nepalsupporting
confidence: 89%
“…Comparisons between inhalational and intravenous anaesthetic agents are difficult, owing to differences in pharmacokinetics, the difficulty in measuring intravenous drug concentrations in real time and the lack of equivalence for intravenous anaesthetics of minimum alveolar concentrations (MAC) of inhalational anaesthetics [35]. The BIS computes segments of EEG and produces an index value that monitors cortical suppression, tracking the changes of effects of anaesthetics on the brain [23].…”
Section: Discussionmentioning
confidence: 99%